Pengaruh BAP dan Sukrosa terhadap Perbanyakan Jahe Empirit (Zingiber officinale Rosc var. amarun) secara In Vitro - Marai Rahmawati; Sandra A. Aziz; Diny Dinarti; Dodo R. Sastra (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
The need to produce numerous and good quality plantlet in short time has been carried out with in vitro culture. The objective of this research was to study BAP and sucrose effect on the in vitro multiplication of small ginger. Research was done in Plant Tissue Culture Laboratory, Department of Agronomy. Bogor Agricultural University from November 2002 until August 2003. The treatment used BAP 0, 1, 2, 3, 4, 5 ppm and sucrose 20, 30, 40, 50 g/l. The result showed that sucrose significantly influenced shoot number in 2-5 and 8 Week After Planting (WAP) and leaf number in 2-7 WAP; root length, root number and explant fresh weight. BAP only significantly influenced leaf number in 7 WAP and root quality. With time shoot color changed from green to yellow. Higher RAP and sucrose concentration increased micro rhizome percentage. Sucrose 40 g/l or RAP 2 ppm gave numerous shoot and high explant fresh weight. Key words : Zingiber officinale Rosc var. amarun, In vitro, BAP, Sucrose